Structural behaviour and design of elliptical high-strength concrete-filled steel tubular short compression members. (15th October 2018) - Hassanein, M.F.; Patel, V.I.; El Hadidy, A.M.; Al Abadi, H.; Elchalakani, Mohamed
Highlights: Elliptical concrete-filled steel tubular (CFST) short columns are investigated. Using ABAQUS, 3D FE elliptical CFSTs under axial and eccentric compression are developed. High-strength concrete is considered. The new design formula yielded the best estimates of strengths of axially-loaded elliptical CFSTs. Abstract: Elliptical concrete-filled steel tubular (CFST) columns have recently attracted significant attention because of their increased strength and stiffness compared with empty elliptical hollow sections (EHSs). As with any new cross-section, there are still many aspects to be investigated to allow for its inclusion in different design specifications. Based on literature survey, this paper investigates the elliptical CFST columns which are filled with high-strength concrete (HSC). Numerical investigations into the structural behaviour of the elliptical CFST columns subjected to pure axial compression and eccentric loading have been performed using the general purpose commercial finite element (FE) software, Abaqus. The validity of the current FE models is examined by comparing their outcomes with those test results in literature. Then, parametric studies are performed considering three main parameters, namely the slenderness of the EHS, the steel yield strength and the concrete compressive strength. This is followed by a discussion of the results, showing in detail the characteristics of their load-strain responses. A comparison of the ultimate strengths with the existing design models is then considered, from which it is found that improved design model could be suggested to save additional weight and reach an optimum design. Hence, a new design formula is presented at the end which considers the effective confined concrete strength. Overall, this investigation expands the available engineering knowledge and assists in utilising the HSC, currently used in a wide range of applications, with the elliptical CFST columns with their favourable aesthetical and structural characteristics.